Big as life stories about men - Cooper, Rand Richards (Dial Press, 1995)
An anthology whose protagonists are mainly men. The stories include Kerenyaga, the observations of a homeless African on life in the U.S., and Magendo Men, the observations of an American teacher on life in Africa. By the author of The Last to Go.